Cost-effectiveness of PET for the management of lung tumours: Comparison of economic data - Dietlein, M.; Moka, D.; Weber, K.; Theissen, P.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2001)
Modelling is an accepted, valid and often necessary method for assessing economic effectiveness in terms of cost per life year gained. Comparing an alternative strategy (a) with a baseline strategy (bl), the incremental cost (C0STa-C0STb|) divided by the incremental life expectancy (LEG-LEbï) defines the incremental cost-effectiveness ratio (ICER). Taking watchful waiting as the low-cost baseline strategy for the management of solitary pulmonary nodules, the ICER of positron emission tomography (PET) [3218 euros (EUR) per life year saved (LYS)] was more favourable than that of exploratory surgery (4210 EUR/LYS) or that of transthoracic needle biopsy (6120 EUR/LYS). Changing the baseline strategy to exploratory surgery, the use of PET led to cost savings and additional life expectancy in case of an intermediate pretest probability of malignancy. For management of potentially operable non-small cell lung cancer the use of PET in patients with normalisized mediastinal lymph nodes on CT was most cost-effective (143 EUR/LYS), and the costs of PET were almost balanced by a better selection of patients for beneficial cancer resection. Using PET in patients with enlarged lymph nodes on CT, the ICER raised to 36,667 EUR/LYS. When PET or CT were positive for mediastinal lymph nodes, the exclusion from biopsy confirmation led to cost savings that did not justify the expected reduction in life expectancy. Economic data from the USA and Japan also demonstrated the cost-effectiveness of PET-based algorithms for the management of lung tumours.
Keywords: Cost-effectiveness; economics; PET; lung